2012
DOI: 10.1021/nl204374v
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Chemical and Structural Characterization of Transient Metallic Nanowires using Aberration-Corrected STEM-EELS

Abstract: Direct chemical and structural characterization of transient iron-nickel alloy nanowires was performed at subnanometer spatial resolution using probe spherical aberration-corrected scanning transmission electron microscopy and electron energy-loss spectroscopy. Nanowires with diameter less than 2 nm retaining their nominal bulk alloy composition were observed. In some cases, the nanowires were oxidized. Before rupture, a nanojunction as thin as three atoms in width could be imaged. The time-dependent structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These composition dependent structural changes at the nanoscale may lead to development of new organic nanoelectronics for the two types of materials. TEM-EELS 48 mapping of the mixed material confirmed the presence of C, H, N and O as constituting atoms (Fig. 2g–j ).…”
Section: Introductionmentioning
confidence: 80%
“…These composition dependent structural changes at the nanoscale may lead to development of new organic nanoelectronics for the two types of materials. TEM-EELS 48 mapping of the mixed material confirmed the presence of C, H, N and O as constituting atoms (Fig. 2g–j ).…”
Section: Introductionmentioning
confidence: 80%
“…The measurements carried out in scanning mode (scanning transmission electron microscopy, STEM), lead to hyperspectral imaging of the region of interest, providing 2D images that contain one full energy‐loss spectrum at every pixel. Thus, we can obtain 2D energy maps at the characteristic plasmon resonances of single NPs and ensembles …”
mentioning
confidence: 99%
“…It might be due to rapid damage (panel B, Figure 2 ) on their organic component-bearing surface by the strong electron-beam of TEM, high reactivity of the metal component of highly oxidation state and/or weak signal generation from the thin nanomaterial. Recently, scanning transmission electron microscope - Electron Energy Loss Spectroscopy (STEM- EELS) is emerging as a powerful tool for elemental mapping of nanomaterials 51 52 53 54 . Our EELS study for the Mn VI -NPs revealed presence of worm-like NPs (panel C, Mn only).…”
Section: Resultsmentioning
confidence: 99%